Strategi Meredakan Sentimen Negatif Surat Keberatan Eiger di Media Sosial; Pendekatan Content Analysis - Dessy Kushardiyanti (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
This study aims to determine how the strategy to reduce the negative sentiment of Eiger's objection letter. This study was analyzed based on the theory of image recovery with descriptive qualitative observation methods, namely analyzing the content of Eiger's Instagram and Twitter posts and the content of followers' comments. The results of this study indicate that Eiger implements an image restoration strategy through social media in order to change public perceptions and attitudes, namely to quickly and accurately respond to apologies through the content of "love letters to Eigerian" as well as direct clarification videos from the CEO who honestly admits his mistakes. without involving or blaming other internal parties on the company. Furthermore, providing maximum and better service in order to gain a positive reputation for Eiger. The results of the study recommend that Eiger can carry out offers of events or social activities such as promos, discounts, give aways or donations by involving CSR and the public, so that companies have a harmonious relationship with the public as users of their products.